Self-Efficacy Perceptions of Tongan Students and Their Teachers Within Year 11 Business Studies - Hausia, Ella’peta Fifita; Matapo, Jacoba; Gaffney, Janet S (Springer Science and Business Media LLC, 2025)
A growing number of Pasifika students are pursuing Business Studies at Secondary school. However, indigenous knowledge and epistemologies are not prominent in Business Studies. We discuss a qualitative decolonising study that explores the concept of self-efficacy in Business Studies from a Tongan perspective. We provide insights into the perceptions of Tongan student’s self-efficacy and their Business Studies teachers. Teachers’ views aligned with Western notions of self-efficacy, which conflict with Tongan perceptions, precisely the collective nature of Tongan self-efficacy. Key findings from teacher interviews and Talanoa with students provided an understanding of Pasifika students in general and experiences specific to Tongan students. Three main themes are highlighted: (a) key values for Tongan students, such as relationships, family, and identity; (b) students’ learning experiences across different contexts; and (c) framings of self-efficacy. This study’s implications for curriculum suggest how teachers can learn from and incorporate Tongan students’ values and identities, enhancing their engagement and performance in Business Studies. Extending this research to include the knowledge and understanding of Tongan families, community leaders, curriculum specialists, Business Studies educators, and researchers would create a transformational space for student engagement. Bringing together shared expert knowledge in the future would require more time for effective and meaningful Talanoa as a collective.
Keywords: 3901 Curriculum and Pedagogy; 3903 Education Systems; 3904 Specialist Studies In Education; 39 Education; 13 Education; Education; Self-efficacy